FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN KOLOSTRUM DI RUMAH SAKIT KHUSUS DAERAH IBU DAN ANAK PERTIWI MAKASSAR - Nurhikmah; yudiarsi eppang (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2021)
Objective: The objectives of the study were to determine the relationship between maternal knowledge level, employment status, family support and health officer support by giving colostrum to newborns by mothers in Maternal and Child Special Hospital Makassar 2019. Method: The design of this study was survey analytic with cross sectional study approach, to know factors related to colostrum administration, with the number of samples 94 by accidental sampling. Discussion: Colostrum is the first fluid secreted by the breast gland, containing debris tissue and material present in the alveoli and ducts of the breast glands before and after the puerperium period. Secreted by breast glands from first to third day. Results: The results concluded that there was a significant correlation between knowledge with the administration of colostrum in maternal women with p value (0.000) ? 0.05, there was a relationship of occupation status with the administration of colostrum with p value (0.000) ? 0,05, there was relation of family support with colostrum with value p (0,001) ? 0,05, there was relation of officer support with giving colostrum to mother with p value (0,015) ? 0,05. Conclusion: there is a relationship of knowledge, job status. Family support, accompanied by officers with the provision of colostrum. Suggestion: It is advisable to need continuous education to mother to give colostrum to baby immediately after delivery. For working mothers should provide time to give colostrum to their babies especially shortly after childbirth, and need to socialize to all family members the importance of giving colostrum to infants to support mothers to provide colostrum in their infants as well as the need for increased motivation for health workers to support mothers maternity to give colostrum to the baby